Determination and evaluation of kinetic parameters of activated sludge biomass from a sludge reduction system treating real sewage by respirometry testing - Karlikanovaite-Balikci, Agne; Yagci, Nevin (Elsevier BV, 2019)
Oxic-settling-anoxic (OSA) process is one of the promising variants that produces lower amounts of sludge and has been applied to aerobic and nutrient removal systems. The only consequence on this modification is that supplementary research is advisable to fully understand the mechanism, which eventually leads to the development of a more realistic model. This study evaluated the characteristics of an OSA process as a sludge reduction system by calibration of kinetic coefficients of ASM1 model with some modifications. A series of respirometric tests were designed for the assessment of microbial kinetics and for further clarification of sludge reduction mechanism. The calibration results depicted that the decay rate is the most variable kinetic parameter depending on the system configuration. It was determined that this kinetic coefficient increased significantly after the system was modified into OSA configuration while other model parameters were almost kept constant. This may be referred to a change either in the microbial population or in the metabolism of the community. The active biomass ratio in the CAS reactor was found to be around 75%, while it was almost 2 times lower in the side-stream reactor. All results led to a conclusion that OSA process is encouraging endogenous decay and consequently lowers biomass viability in the reactor and achieves excess sludge reduction in the system. All experimental results confirmed that side-stream reactor accelerates decay rate of the community and causes the introduction of sludge with low viability to the main reactor.
Keywords: Kinetics; Bioreactors; Sewage; Biomass; Waste Disposal, Fluid